A Multi-Pier MP method for the non-linear static analysis of out-of-plane loaded masonry walls. (15th November 2020) - Pirsaheb, Hiva; Javad Moradi, Mohammad; Milani, Gabriele
Highlights: Multi-Pier MP method for the out-of-plane pushover analysis of masonry walls. In MP the 2D wall is substituted with trusses with equivalent mechanical properties. Possibility to implement directly the model in a commercial software. Satisfactory fitting of pushover curves and crack patterns with limited effort. Direct utilization in design without the need to implement ad hoc constitutive equations. Abstract: The aim of this paper is to propose a novel 3D truss-like approach called Multi Pier (MP) to analyze the out-of-plane non-linear static behavior of masonry walls. The use of truss elements allows the model to be time-saving, accurate and implementable into a commercial FE software equipped with only non-linearity for 1D elements; consequently, it is characterized by a drastic reduction of the computational effort required and by impressive robustness, being possible an immediate utilization by inexperienced users. In the model, the wall is divided in the horizontal and vertical directions into 3D braced truss frames, with horizontal and vertical elements called piers and diagonal elements called braces. The axial, flexural, and torsional behavior, and their mutual interaction at the meso -scale level (masonry unit cell) are accurately reproduced. Nine experimental masonry walls in two-way bending, in presence or absence of openings and complex boundary conditions, are numerically analyzed to assess the ability of the model at a structural level to reproduce global load–displacement curves obtained experimentally and crack patterns at collapse. A satisfactory match between numerical predictions and experimental evidence is systematically found, meaning that the procedure proposed can represent a simple and valuable tool for all those practitioners not familiar with advanced computations in masonry field, but interested in a reliable prediction of the behavior of masonry walls out-of-plane loaded by means of standard commercial codes.